Bullous Cellulitis Due to Coagulase Negative Staphylococcus in Immunocompromised Patient - Septina Yosephine; Dhelya Widasmara; Anggun Putri Yuniaswan (Asian Journal of Health Research, 2024)
Introduction: Bullous Cellulitis is initially characterized by erythema and rapid development of bullae. This disease is most often caused by Beta-hemolytic streptococci and rarely by other bacteria such as Coagulase-Negative Staphylococcus (CoNS) type Staphylococcus haemolyticus. Immunocompromised state and history of malignancy are at high risk of infection with this bacterium. Local complications such as bullae can occur in obesity. Case Presentation: A 48-year-old woman with complaints of tensed and loose-walled blisters with a reddish base on the right thigh. The patient had a medical history of Thyroid Cancer, Acute Renal Failure, and Bulging Mass pelvic femur. On physical examination, the patient was unconscious with a ventilator. Dermatological examination of the dextra inferior extremity showed loose bullae with a positive Nikolsky sign and tensed bullae over the erythematous patches, ill-defined, irregular edges, and warm palpable. Laboratory results of leukocytosis, hypoalbumin, and CoNS bacteria from blood culture. An ALT-70 score obtained a total score of 5. Conclusion: Cases of bullous cellulitis are quite rare; cases like this usually occur in patients with an immunocompromised predisposition and obesity. CoNS is a commensal bacteria but, in some cases, could be a pathogen causing cellulitis. Poor prognosis that ends in death could occur in patients who have various complications.